MODERN HINDUISM IN TEXT AND CONTEXT - Vemsani, Lavanya (BLOOMSBURY ACADEMIC, 2018)
Introduction / Lavanya Vemsani -- Traditional Hinduism: classical texts, traditions, and practices -- Multi-regional and multi-linguistic virasaivism: change and continuity in an early devotional tradition / Elaine Fisher -- Entering the South Asian city: Pravesa in literature and religion / Michael Baltutis -- Demonic devotees and symbolism of violence in Hindu literature / Carl Olson -- Sacred groves: the playground of the gods / Deepak Shimkhada and Jason Mitchell - Religious symbolism of sacrificial blood in contemporary political art: myth and art in Tamil popular culture / Amy-Ruth Holt -- Hinduism in the modern world: colonial, diasporic and women's religion -- Rite of passage in India's national struggle: understanding ravindranath Tagore's gora in the context of religion -- America, the superlative, and India, the jewel in the crown: religious ideologies, transnationalism, and the end of the raj / Deborah A. Logan -- The integral yoga of the Sri Aurobindo Asram: gender, spirituality, and the arts / Patrick Beldio -- In relationship with the goddess: women interpreting leadership roles and shaping diasporic identities / Nanette R. Spina -- Spirituality and ritual in Odissi dance: health, healing, and ritual in a diaspora performance tradition / Kaustavi Sarkar -- A mandal of their own: gender and the reimagining of community by Hindu renouncers in North India / Antoinette E. Denapoli -- Conclusion / Lavanya Vemsani -- Appendix -- Glossary